Infancy pending between life and death. Theology and Law on the fate of unbaptized dead infants (Italian Review of Legal History, 2019)
In the Christian faith the death of unbaptized children represented an inconsolable double pain for their parents. As Baptism is the first holy sacrament to welcome newborns into the Catholic life and to free them from the original sin they were born with, death before baptism meant no soul’s salvation and Hell’s damnation. Thus, dead unbaptized infants could not be buried in consecrated ground, and parents could not pray for their soul. From the 13th century on, by stating the existence of the Limbo – an intermediate space between Heaven and Hell – the Thomistic doctrine tried to mitigate the strictness of the Augustinian doctrine on the subject, even not solving the problem of a proper burial in consecrated ground.Sources and doctrinal debates tell a story of a centuries-old difficulty of the Western Church and its institutions in providing a definite solution to this problem even in its juridical implications. Indeed, there were also numerous legal and forensic medical aspects linked to unbaptized dead infants. For centuries, Baptism represented the first – and sometime the only – official registration of a newborn, who otherwise remained unknown. Thus, a delay or absence of baptism could conceal a new birth as well as an infanticide.Especially after the Counter-Reformation, the Church promoted an intense campaign to push priest, midwives and accoucheurs to baptize future child in case of dangerous births. This resulted in a debate on cesarean section and other medical or popular practices that could menace mothers’ life by virtue of fetus’ baptism. The main point was to choose between the life of the mother and the right of the fetus to life and health, and between the mother’s physical health and child’s spiritual health. Over time, some popular beliefs took root aimed to relief the pain of dead unbaptized infants’ parents. Among these, the belief of the miracles of “répit” or “double death” sanctuaries. According to some local traditions, children who died unbaptized – thanks to prayers by pious women or hermits – could “resurrect” for a brief time necessary to be baptized. Then, they died “again” and could definitively rise to divine grace. This alleged miracle, never confirmed in any official process, became a matter of discussion among the ecclesiastical authorities. At the same time, it pushed the grieving parents to return to their communities with documents – often formally drafted and signed by local notaries – which certified the “resurrection”, the baptism and the new death. These documents allowed dead children to be regularly buried and proved that the family had done everything possible to guarantee their children salvation in order to rejoin them in the afterlife.
Keywords: Limbo, baptism, cesarean section, burials, forensic medicine; limbo; baptism; cesarean section; burials; forensic medicine